Cognitive learning outcomes with an inquiry learning model assisted by Macromedia Flash material on plant structures - Leasa, Marleny; Lewier, Meltina Agnes; Maelan, Marni (Universitas Negeri Jakarta, 2022)
The inquiry learning model (IBL) has been explored in many fields of science. Therefore, this research shows the exploration of IBL assisted by Macromedia flash in improving cognitive science learning outcomes for elementary school students. This study aimed to determine the effect of Macromedia flash-assisted IBL on students' cognitive learning outcomes. This quasi-experimental research with a nonequivalent control group design used a sample of 66 students consisting of 33 students in the experimental group and 33 students in the control group. The data collection technique was carried out through tests, using test questions validated by experts and tested for feasibility. Hypothesis testing by the ANCOVA test analysis using the SPSS Statistics 23 program on the pretests obtained a sig value. (2-tailed) > which is 0.000 <0.05, then H0 is rejected, and Ha is accepted. It means that there is an influence of the learning model on cognitive learning outcomes. The results of the LSD test showed that the IBL model assisted by Macromedia flash was significantly different in cognitive learning outcomes compared to the conventional model. Thus, IBL Macromedia flash assistance can be recommended for improving students' cognitive learning outcomes.